Exposome, oxidative stress and inflammation in persons with multiple sclerosis: the EXPOSITION study protocol - Monti, Maria Cristina; De Giuseppe, Rachele; Bertoli, Gloria; Alemayohu, Mulubirhan Assefa; Al-Naqeb, Ghanya; Ballante, Elena; Bergamaschi, Roberto; Camboni, Tania; Ceccarani, Camilla; Ceriani, Chiara; Colombo, Elena; Consolandi, Clarissa; et al. (Frontiers in Public Health, 2025)
The exposome represents the totality of external and internal exposures an individual encounters throughout life and plays a critical role in developing many chronic diseases, including multiple sclerosis (MS). MS is a multifactorial disease influenced by both genetic and environmental factors. The EXPOSITION study (registered on www.clinicaltrials.gov, NCT06325358) aims to investigate the association between environmental exposures (external exposome) and biological markers of oxidative stress and inflammation (internal exposome) in people with MS. This cross-sectional study will involve 200 individuals with MS, assessed for lifestyle and occupational variables and biological markers, including circulating microRNAs, neurofilament light chains, pro- and anti-inflammatory cytokines, and gut/nasal microbiota composition. The study will use advanced statistical models, such as generalised linear models and multivariate analyses, to assess associations between external exposures and biological outcomes. By integrating both environmental and biological factors, this research aims to deepen our understanding of MS mechanisms, providing insights that could lead to targeted interventions, personalised therapies, and public health strategies to mitigate MS progression.